1990
DOI: 10.1063/1.345721
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of ion energy distributions at the powered rf electrode in a variable magnetic field

Abstract: High-resolution energy distributions of ions, accelerated by the sheath at the powered electrode of a low-pressure 13.56-MHz gas discharge, have been measured. The observed spectra are compared to existing models. Excellent agreement between measured and calculated spectra is obtained. Detailed information on rf sheath behavior is derived from the observed energy profiles and from the measured total ion current densities towards the electrode surface. Analogous to the case of dc discharges, a decrease of sheat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(53 citation statements)
references
References 33 publications
0
53
0
Order By: Relevance
“…In deposition by sputtering, the stoichiometry of Cu 2 O is retained by the ratio of the partial pressure of the reactive gas over the flux of Ar, Φ(Ar), that erodes the target surface [12]. At a fixed Q(Ar) inlet, Φ(Ar) depends on the sheath potential/target potential [15], which is correlated to the target power [16]. Once the partial pressure of Ar and O 2 are set, the flux of the non-reactive gas and consequently the balance of Cu versus O atoms accumulated on the substrate will be controlled by the target power during the reactive sputtering process.…”
Section: Introductionmentioning
confidence: 99%
“…In deposition by sputtering, the stoichiometry of Cu 2 O is retained by the ratio of the partial pressure of the reactive gas over the flux of Ar, Φ(Ar), that erodes the target surface [12]. At a fixed Q(Ar) inlet, Φ(Ar) depends on the sheath potential/target potential [15], which is correlated to the target power [16]. Once the partial pressure of Ar and O 2 are set, the flux of the non-reactive gas and consequently the balance of Cu versus O atoms accumulated on the substrate will be controlled by the target power during the reactive sputtering process.…”
Section: Introductionmentioning
confidence: 99%
“…7-10 Cook and Donohoe 11 suggested that methods must be developed to control the energies and ion fluxes of species in discharges for the benefit of future semiconductor devices, due to the effect energetic species have on the nature of materials when they are bombarded by such species. To understand the role of plasma species in a discharge, theoretical [12][13][14] and experimental [15][16][17][18][19] studies of the Ion Energy Distribution (IED) of particles in a deposition discharge have been under taken and reported. However, most of these studies focused on Ar þ ions since argon is generally the gas used in sputtering discharges and also because of the relative simplicity of its chemical kinetics in such plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…5. The experimental date (curves b) were taken from Kuypers et al [3]; the calculated distribution functions (curves a) were folded with a Gaussian of 3 eV standard deviation, in order to represent the limited energy resolution of the mass spectrometer.…”
Section: The Hybrid Boundary Sheath Modelmentioning
confidence: 99%